1995
DOI: 10.1164/ajrccm/151.3_pt_1.887
|View full text |Cite
|
Sign up to set email alerts
|

Latex Gloves with a Lower Protein Content Reduce Bronchial Reactions in Subjects with Occupational Asthma Caused by Latex

Abstract: Latex gloves have been documented as causing rhinitis and asthma. Using inhalation challenges, we evaluated the bronchial response to hypoallergenic gloves in eight health care workers with latex-induced asthma. The subjects were exposed to the powdered latex gloves causing asthma at work and various brands of gloves with a lower protein content, either low-powdered, nonpowdered, or powdered. Exposure to hypoallergenic gloves resulted in the absence (in six subjects) or a significant reduction (in two subjects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…They applied latex glove extracts in increasing concentrations and assessed the clinical response and spirometry. Currently, this test may be performed with the use of atomized latex extract [23] and is considered useful for the diagnosis of occupational allergy in particular working conditions [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…They applied latex glove extracts in increasing concentrations and assessed the clinical response and spirometry. Currently, this test may be performed with the use of atomized latex extract [23] and is considered useful for the diagnosis of occupational allergy in particular working conditions [23,24]. …”
Section: Discussionmentioning
confidence: 99%
“…Many hospitals have worked toward the goal of a latex-safe environment by attempting to eliminate all powdered and in some cases nonpowdered latex medical gloves. [4][5][6]12,13 Although most have been successful with conversion of powdered nonsterile latex examination gloves to synthetic alternatives, it has been more difficult to get surgeons to convert from powdered sterile surgical gloves to nonpowdered or synthetic alternatives. 14 The cited reasons for this include barrier protein concerns, leakage rates, undesirable tactile characteristics, and cost.…”
Section: Discussionmentioning
confidence: 99%
“…OR has been well-described in health care workers [1, [17][18][19]. Natural rubber latex (NRL) and psyllium are commonly associated with OR in health care workers.…”
Section: Specific Causes and Occupationsmentioning
confidence: 99%
“…Studies have shown that strategies to reduce occupational exposure have successfully decreased OR symptoms in cases of OR caused by NRL [18] and proteolytic enzymes [37]. Steps to modify the workplace could include providing adequate ventilation and aspiration of pollutants, using less hazardous materials, and creating closed-circuit manufacturing processes.…”
Section: Managementmentioning
confidence: 99%